FENOMENA KOMUNIKASI OVERSHARING DALAM VIDEO IKLAN LAYANAN MASYARAKAT - Muhamad Lutfi Habibi (Indonesian Journal of Islamic Communication, 2021)
Background problem in this research is how the Komunikasi Oversharing representation contained in public service advertisement video "Saring Sebelum Sharing" produced by Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia (Kemdikbud RI). The analysis unit in this study is signifiers and signifieds that produce signs contained in every scene which are identified through Bernard F. Dick’s anatomy of film. This research method uses Roland Barthes’ denotative and connotative semiotic analysis. The results show that the Komunikasi Oversharing representations can be grouped into four meanings in each scene, that is teenagers’ tendency to do not think ahead, the speed of social media in spreading the information, surveillance capitalism, and the capability of algorithm system to targeting lookalike audiences.